The Effect of Liquidity, Leverage, and Profitability on Financial Distress Using the Altman Z-Score Approach in Oil and Gas Companies Listed on the Indonesia Stock Exchange (IDX) During the 2021–2024 Period - Haninda Alya Rafida; Dody Kurniawan; Cahyadi Husadha (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study aims to examine the effect of liquidity, leverage, and profitability on financial distress using the Altman Z-Score approach in oil and gas companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Liquidity is proxied by the Current Ratio (CR), leverage by the Debt to Equity Ratio (DER), and profitability by Return on Assets (ROA). This study employed a quantitative approach with a purposive sampling technique, resulting in a sample of 13 companies. The analytical methods employed included descriptive statistics, panel data regression analysis, and classical assumption testing, including tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. Hypothesis testing was conducted using partial t-tests using EViews 12 software. The results showed that liquidity negatively impacted financial distress, leverage positively impacted financial distress, and profitability negatively impacted financial distress. This suggests that increasing liquidity and profitability can reduce the potential for financial distress, while increasing leverage actually increases the risk of financial distress.